Pengaruh Maqashid Syariah Index, Islamicity Performance Index dan Debt Equity Ratio terhadap Profitabilitas dengan Intellectual Capital sebagai Variabel Moderating pada Bank Umum Syariah di Indonesia - Izati, Hanifa Al; Nengsih, Titin Agustin; Rahman, Fuad; Mubyarto, Novi (Universitas Batanghari Jambi, 2024)
This study aims to determine and test the effect of the Sharia Index Maqashid Index, Islamic Performance Index, and Debt Equity Ratio on the profitability of sharia commercial banks in Indonesia, using intellectual capital as a moderation variable. This study uses quantitative research methodology and takes secondary data from the annual financial statements of Indonesian Sharia Commercial Banks in 2018-2022. The sample of eight banks was selected through the use of purposive sampling. Data analysis techniques are called Moderated Regression Analysis (MRA). The results of this study are as follows: (1) Sharia Maqashid Index has no influence on profitability; (2) Islamic performance index has an influence on profitability; (3) Debt Equity Ratio has a negative influence on profitability; (4) Intellectual Capital can moderate the influence of the Sharia Maqashid Index on profitability; (5) Islamic performance index of profitability cannot be moderated by intellectual capital; and (6) Intellectual Capital can moderate the effect of debt equity ratio on profitability.